The fundamental human right to social security in the Portuguese Constitution and how needs of funding are pursued - Marco António Cabeçais de Carvalho (Prawo Budżetowe Państwa i Samorządu)
The right to social security has been a theme of attention and debate, not only regarding its nature, but also how it is to be accomplished and ensured. This article intends to contribute to this discussion by stating, in the Author’s opinion, what is the nature of the right to social security and how the Portuguese State has created its system to accomplish the duty that is set upon on it. This system is thrice divided and subsequently composed of subsystems and different regimes. Furthermore, the Author also analyses the established forms and sources of financing needs of social security, and verifies how these are allocated to the different systems, without disregarding the needs that they could have in acquiring a balance between them. Lastly, it is discussed how the public capitalization system with Social Security Financial Stabilization Fund was created to act as a reserve fund and as a safety net of the contributory system of the social security system.